2019
DOI: 10.5194/isprs-annals-iv-2-w6-123-2019
|View full text |Cite
|
Sign up to set email alerts
|

Between Images and Built Form: Automating the Recognition of Standardised Building Components Using Deep Learning

Abstract: Building on the richness of recent contributions in the field, this paper presents a state-of-the-art CNN analysis method for automating the recognition of standardised building components in modern heritage buildings. At the turn of the twentieth century manufactured building components became widely advertised for specification by architects. Consequently, a form of standardisation across various typologies began to take place. During this era of rapid economic and industrialised growth, many forms of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Previous work has confirmed this hypothesis through a comparative test of the performance (measured class-by-class using the relative F1-scores) of 3 different machine learning architectures in the classification of different ventilation building components [70]. The results indicated that a Feature Pyramid Network classification model (FPN, Figure 3) outperforms a high-end Traditional Machine Learning model (TML) composed of SIFT, K-means clustering and standard RF, by an average 26% on all the 4 examined classes of objects.…”
Section: Identifying Patterns: Matching and Recognitionmentioning
confidence: 77%
“…Previous work has confirmed this hypothesis through a comparative test of the performance (measured class-by-class using the relative F1-scores) of 3 different machine learning architectures in the classification of different ventilation building components [70]. The results indicated that a Feature Pyramid Network classification model (FPN, Figure 3) outperforms a high-end Traditional Machine Learning model (TML) composed of SIFT, K-means clustering and standard RF, by an average 26% on all the 4 examined classes of objects.…”
Section: Identifying Patterns: Matching and Recognitionmentioning
confidence: 77%
“…Deep learning allows machines to learn from pixels to classifiers. Each layered layer with a similar structure performing different transformation functions pulls features from layers below and above in a directly connected way [33]. In Digital Cultural Heritage (DCH), semantic segmentation of 3D Point Clouds with Deep Learning (DL) techniques can help recognise historical architectural elements at an adequate level of detail, speeding up the process of modelling historical buildings for developing BIM models from survey data, called HBIM (Historical Building Information Modeling) [28].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the incorporation of regulations, such as the system of rates for buildings in London which determined eighteenth century window sizes, wall thicknesses and storey heights for the purposes of taxation and fire protection, may also enhance the capacity of heritage-related parametric library objects. As might the deployment of deep learning in relation to the information contained within historic building catalogues (Prizeman 2016;2019, Pezzica et al 2019. This latter notion has previously been explored in the development of visual matching techniques for early 20 th century Carnegie Library buildings (Prizeman et al 2018).…”
Section: Discussion -Future Workmentioning
confidence: 99%